PENGUJIAN REAKSI PASAR TERHADAP PERISTIWA MERGER DAN AKUISISI DI BURSA EFEK INDONESIA (BEI) - Malau, Rintohan; Wiagustini, Luh Putu; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.09.TAHUN 2017, 2017)
This study aimed to see whether there abnormal returns around the period of mergers and acquisitions, using a market model and the expected returns of 100 days, as well as using the event period is seven days before and seven days after the announcement of mergers and acquisitions. The sample was a company for mergers and acquisitions in Indonesia Stock Exchange during the years 2013-2015, sampling in this study did not consider the corporate Action others besides mergers and acquisitions alone, so it acquired 30 companies as the sample material, the analysis tools used in this research is multiple linear regression with Level of Singnificance by 5%. The results showed that there were no abnormal returns around the period of the study, so it can be said that there is no market reaction around the announcement of mergers and acquisitions as evidenced by a greater significance than 0.05%. Most likely this is because there is no leakage of information during the period of the study.
Keywords: Abnormal Return, Mergers, Acquisitions, Average Abnormal Return, Efficiency-Market